POTENSI DAS KAHAYAN SEBAGAI RUANG HIJAU DALAM PERENCANAAN KAWASAN TERPADU KOTA PALANGKA RAYA - Noor Hamidah; Mahdi Santoso (Universitas Negeri Yogyakarta, 2010)
Kahayan’s watershed have a potential area of green space as the first steplarge enough to maintain the sustainability of green space. This watershed is animportant part to absorb global warming and structuring integrated area Palangkaraya in Central Kalimantan province. The presence of green space will be needed in an integrated region planning Palangkaraya to compensate for the density of buildings. Various forms of green space activities in general are as shade from the warm environment, and as receptacles for the city of Palangkaraya community to socialize and interact with nature. Fulfillment of green areas in the city of Palangkaraya is an initial effort to grow awareness of the environment in terms of aligning the media downturn availability of clean air and healthy due to natural degradation in Palangkaraya. The concept of integrated area planning Palangkaraya by relying on the potential of green space Kahayan’s watershed is expected to balance between vegetation and the presence of alignment with the ecological environment constructionof city infrastructure, so that will achieve the purpose of applying the concept ofsustainable development and is also able to overcome the problem of global warming are felt at this time.Keywords: Potential, Kahayan’s watershed, Integrated Area Green Space,Palangkaraya